(untitled) (Journal of Health, Population and Nutrition, 2010)
An isolated area with diarrhoea epidemic was explored at Pakhirala village of the Sundarbans, a coastal region of South 24 Parganas district of West Bengal, eastern India. The Pakhirala village was surrounded by other villages affected by a similar epidemic. The affected villages experienced this epidemic following the cyclone Aila, which had hit the coastal region of the Sundarbans in eastern India. In Pakhirala, the situation was the worst. Within a span of six weeks (5 June–20 July 2009), 3,529 (91.2%) of 3,871 residents were affected by watery diarrhoea. Of all the cases (n=3,529), 918 (26%) were affected by moderate to severe diarrhoea. In other villages, 28,550 (70%) of the 40,786 people were affected; of them, 3,997 (14%) had moderate to severe watery diarrhoea. The attack rate and the severity of the cases were significantly higher in Pakhirala village compared to other affected villages. The laboratory results revealed that Vibrio fluvialis was the predominant pathogen in Pakhirala village (5 of 6 laboratory-confirmed organisms) whereas Vibrio cholerae O1 Ogawa was the predominant pathogen in other villages of Gosaba block (7 of 9 bacteriologically- confirmed organisms). This result indicates that V. fluvialis behaves more aggressively than V. cholerae O1 in an epidemic situation with a higher attack rate and a different clinical picture. An in-depth study is required to explore its pathogenicity in detail, geographical distribution, and possible control measures, including development of specific vaccine preparation and determination of its efficacy. Key words: Diarrhoea; Cyclone; Disasters, Natural; Vibrio cholerae; Vibrio fluvialis; India DOI: 10.3329/jhpn.v28i4.6037 J HEALTH POPUL NUTR 2010 Aug 28(4):311-317